Are Small Nucleolar RNAs "CRISPRable"? A Report on Box C/D Small Nucleolar RNA Editing in Human Cells - Julia A. Filippova; Anastasiya M. Matveeva; Anastasiya M. Matveeva; Evgenii S. Zhuravlev; Evgenia A. Balakhonova; Daria V. Prokhorova; Daria V. Prokhorova; Sergey J. Malanin; Raihan Shah Mahmud; Tatiana V. Grigoryeva; Ksenia S. Anufrieva; Ksenia S. Anufrieva; et al. (Frontiers Media S.A., 2019)
CRISPR technologies are nowadays widely used for targeted knockout of numerous protein-coding genes and for the study of various processes and metabolic pathways in human cells. Most attention in the genome editing field is now focused on the cleavage of protein-coding genes or genes encoding long non-coding RNAs (lncRNAs), while the studies on targeted knockout of intron-encoded regulatory RNAs are sparse. Small nucleolar RNAs (snoRNAs) present a class of non-coding RNAs encoded within the introns of various host genes and involved in post-transcriptional maturation of ribosomal RNAs (rRNAs) in eukaryotic cells. Box C/D snoRNAs direct 2'-O-methylation of rRNA nucleotides. These short RNAs have specific elements in their structure, namely, boxes C and D, and a target-recognizing region. Here, we present the study devoted to CRISPR/Cas9-mediated editing of box C/D snoRNA genes in Gas5. We obtained monoclonal cell lines carrying mutations in snoRNA genes and analyzed the levels of the mutant box C/D snoRNA as well as the 2'-O-methylation status of the target rRNA nucleotide in the obtained cells. Mutations in SNORD75 in the obtained monoclonal cell line were shown to result in aberrant splicing of Gas5 with exclusion of exons 3 to 5, which was confirmed by RT-PCR and RNA-Seq. The obtained results suggest that SNORD75 contains an element for binding of some factors regulating maturation of Gas5 pre-lncRNA. We suggest that METTL3/METTL14 is among such factors, and m6A-methylation pathways are involved in regulation of Gas5 splicing. Our results shell light on the role of SNORDs in regulating splicing of the host gene.